Odol Law Enforcement in Suppressing Traffic Accidents in Gorontalo Regency: An Empirical Study - Nurhalisa Kasim; Fenty U. Puluhulawa; Muhamad Khairun Kurniawan Kadir (al-Battar: Jurnal Pamungkas Hukum, 2026)
Vehicle over Dimension over Loading (ODOL) is one of the main factors causing traffic accidents in Gorontalo Regency. Although it has been regulated in legislation, law enforcement has not been running optimally, so there is a research gap because the previous study focused more on normative aspects and has not assessed its effectiveness empirically at the regional level. This study aims to analyze the effectiveness of ODOL law enforcement in suppressing traffic accidents and identify inhibiting factors. The method used is empirical legal research with a qualitative approach, using soerjono Soekanto's theory of legal effectiveness and Hans Kelsen's theory of legal norms. Data were obtained through interviews and literature studies. The results showed that ODOL law enforcement has not been effective, which is influenced by low legal awareness of the community, weak supervision, limited facilities and infrastructure, economic interests of business actors, and not optimal coordination between agencies. The implications of this study emphasize the need for firm and consistent law enforcement, increasing public awareness, and strengthening coordination and support facilities to reduce ODOL violations and the risk of traffic accidents.